How Italian metropolitan cities are dealing with the issue of climate change? The study cases of metropolitan cities of Bologna, Milan and Venice. - Molinaro, Walter (TeMA - Journal of Land Use, Mobility and Environment, 2020)
In recent decades, climate change has become one of the most discussed topics within the territorial planning debates, both at European and Italian level. Urban and territorial planning addresses the topic in different ways according to the territorial and legislative context and according to the level of government of the territory involved. In the following article, firstly, the role of planning at European level in the fight against the negative effects of climate change is defined. Subsequently the focus is shifted to the Italian territorial context; in particular, to the role that the level of government of the metropolitan area, introduced in 2014 with the law 56/2014, better known as the Delrio Law, can play within these environmental challenges. Although the Italian metropolitan cities are widely differing in terms of territory, population and economy, they can represent, according to some visions, a potential pivot for the development of the entire nation. In 2017, Italian metropolitan cities signed the ''Bologna Charter'', a document that places them as protagonists of environmental protection and sustainable development. By means of this document, metropolitan cities undertake to counteract the negative effects of climate change by achieving eight macro objectives. The process of analysis of metropolitan cities and their planning tools has enabled the identification of virtuous metropolitan planning cases, which were found to be those of the Metropolitan Cities of Bologna, Milan and Venice. Subsequently, the actions that the three metropolitan cities have in order to achieve the eight objectives of the Bologna Charter, were analyzed. Precisely through this critical reading, it was possible to identify the best practices implemented. The topics most dealt within the metropolitan strategic plans are: sustainable mobility, energy efficiency, prevention of the effects of climate change, urban green areas and the protection of biodiversity. In relation to these issues, the three selected case studies implement noteworthy actions, which have been identified as possible models for other metropolitan bodies. The conclusion reached at the end of this analysis and comparison work, appears to be the belief that Italian metropolitan cities could actually play a coordinating role in climate change policies, promoting an integrated approach to spatial planning. To ensure that this result can be achieved, the promotion of a strong integration between the level of government of the metropolitan area and the local one is necessary. The latter, in fact, is indicated by supranational policies as the most suitable for dealing with the problem of climate change. The further conclusion reached concerns the importance of the mayor in this context. This figure is the most suitable for implementing the integration between the two levels of government of the territory. The Delrio Law establishes, indeed, that the mayors of the metropolitan bodies coincide with those of the main town.